The Role of Midazolam on Status Epilepticus: Systematic Review - Firdha, Azizah Amimathul; Puspamaniar, Vania Ayu; Machin, Abduloh (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Status epilepticus is a condition that results either in the failure of the mechanisms responsible for stopping seizures or in initiating mechanisms that cause seizures to be abnormally prolonged. Benzodiazepine is the first-line therapy for status epilepticus. The three usually used Benzodiazepines are Lorazepam, diazepam, and midazolam. Objective: This systematic review was undertaken to determine midazolam's role in managing patients with status epilepticus. Methods: A systematic search from PubMed, Science Direct, and Cochrane was conducted with predetermined keywords. Studies in randomized controlled trials assessing the impact of midazolam on epileptic status were included in the inclusion criteria. Articles are published in English, and the full text is accessible. The authors independently extracted data and assessed the risk of bias for each included study. Results: Of 6410 studies obtained from the search results, 13 studies were found that were relevant and matched the inclusion criteria. Benzodiazepines are the first line of SE therapy in an emergency. This group works by inhibiting GABA receptors and has a rapid effect in stopping seizures. Midazolam can be given intravenously, intramuscularly, or transmucosal (nasal, buccal, or rectal). Intravenous midazolam may be a good choice because of its short onset of action and, therefore, can effectively stop seizures. Conclusion: Effective and safe results have been seen with each Midazolam administration method. This suggests that Midazolam may be an excellent therapeutic option for SE. However, the type of Midazolam administration can be adjusted according to the guidelines and drug availability in each country.